The Effect of Capital Working Management on the Profitability - Slamet Mulyono; Djumahir Djumahir; Kusuma Ratnawati (Jurnal Keuangan dan Perbankan, 2018)
Companies must maintain the sustainability business. In order to keep their existence and competitiveness, companies must increase profitability in every year. It also applies to state fertilizer companies. However, 10 years of history (2005-2014), the state fertilizer company have been facing difficulties in maintaining business sustainability. Profitability fluctuates and tends to decrease every year. One of the causes is inefficient working capital management. The objective of this study is to determine the relationship between working capital management and corporate profitability. To ensure the absence of the influence of unexamined factors, this study uses control variables of firm size, financial leverage, and gross domestic product. This research uses a positivist paradigm with a quantitative approach and multiple regression analysis. The results of this study indicate that state fertilizer companies will be able to increase ROA by accelerating Days of Sales in Inventory and Days of Payables. Higher assets, reduce profitability, and increasing debt withdrawal, which further declines profitability. State fertilizer companies should accelerate inventory turnover and obligation payments to suppliers to minimize the risk of foreign exchange loss, considering that 80% of raw materials are still imported. In addition, state fertilizer should maintain asset quality and minimize debt withdrawal to increase profitability.JEL Classification: G02; G31DOI: https://doi.org/10.26905/jkdp.v22i1.1332